Política de valorização dos profissionais da educação básica na rede estadual de ensino do Pará - SOUZA, Michele Borges de (Universidade Federal do Pará, 2012)
This research deals with the policy of Teachers in Public Elementary Education, having as object of analysis the Law No. 7442 of July 2, 2010, which provides for the Career Plan, Career and Remuneration (PCCR) of professionals in Basic Education of the state of Pará. Specifically sought are: Identify the context, origins, and the grounds on which national policies were developed in Brazil for the upgrading of Basic Education professionals from the year 1990; Identify and analyze the Basic Education Policy in the State of Pará in the period 2007 to 2010 and its decisions to Career Plan, Career and Remuneration as an instrument for the upgrading of Basic Education professionals; Analyze Law n º 7.442/2010 the light of the theoretical value for the teaching of Basic Education with regard to career, remuneration and working hours. For this research we start from a literature search on the valuation of public teaching, career, working conditions and initial and continuing training. The procedure consisted of theoretical and methodological research a documentary character based on federal and state laws, involving legal and technical documents that were crucial to this investigation, as conference papers, conferences, educational books, among them, CONAE, CNTE, ANPEd, and ANFOPE SINTEPP. The conclusions reached can be inferred that although during the period 2007-2010 has been prepared a guidance document for the Basic Education Policy in Pará State, from the State Plan for Education, bearing in mind the issue of valuation of professional education of the state and within this the intention of deploying a Career Plan, Career and Remuneration, this path was full of great political and ideological clashes between two proposals, government and union and greater than has been the struggle to adopt a unified and PCCR to ensure direct earned, this, in its implementation, revealed itself as an instrument of little value to ensure the viability of the public teaching of Pará.